A study of the preferred learning styles of students taking the English 1119 paper in SMK Tengku Intan Zaharah: are the teachers aware of these learning styles? / Wan Raihan Wan Shaaidi - Wan Shaaidi, Wan Raihan (2012)
Some students prefer to learn by themselves in their own pace, in familiar surrounding rather than in groups. Students tend to perceive information differently, such as by "viewing and listening, reflection and action, to reasoning logically and intuitively and also scrutinizing and visualising" (Felder & Henriques, 1995). This has resulted in education institutions paying great detail to students' learning styles to nurture them to be responsible towards their own learning process. With this in mind, a study was conducted to investigate the most preferred learning styles of students taking English 1119 paper in SMK Tengku Intan Zaharah and if the teachers were aware of these learning styles. More specifically, the study aims to identify the most preferred learning styles of students learning the 1119 English paper according to gender and academic streams (Pure Science and Account). In addition, this study investigated whether their teachers are aware of the learners' language learning needs. This study was carried out among 60 selected form 4 students and 48 form 5 students selected using cluster random sampling. A questionnaire was used for the students, adapted from Perceptual Learning Styles Preferences (PLPS) Survey by Joy Reid (1984) while for the teachers, the researcher used a closed format questionnaire adapted from Brindley (1984). Data were analysed and presented in the form of descriptive statistics, frequency and independent T-tests. This research found out that the most preferred learning styles of the students is Visual learning style while the major factor that influenced their learning style is that they are 'digital natives'. Finally, this study revealed that the teachers were aware of the students' preferred learning style and tried their best to match their teaching styles to suit the students' preferences. From these findings, a few recommendations suggested that it is crucial to understand the importance of learning styles, to be effective and sensitive in teaching styles, to have flexible and wide-ranging instructional planning, and use diversity of teaching aids.